Tindak Tutur Presiden Jokowi yang Terpilih pada Media Sosial Twitter - Anugrah Sari; Ikhwan, M Said; Gusnawaty Gusnawaty (Universitas Cokroaminoto Palopo, 2022)
In this study, the researcher focused on examining the speech acts used by the 7th Indonesian President, Ir. H. Joko Widodo or known as Jokowi on his official account on Twitter. This study is aimed to (1) Describe what types of speech act used by Jokowi on Twitter, and (2) Describe about the factors of situation that underlying the use of Jokowi’s speech act on Twitter. The technique used in retrieving the required data is the purposive sampling technique and based on the speech act theory of Austin. It is ramified for three types, namely locutionary act, illocutionary act, and perlocutionary act. This study used a descriptive qualitative method to clarify the problems by using qualitative data that produced descriptive data. The technique of collecting the data referred to the theory of Miles and Huberman (1994) which is divided into four as follows (1) Data collection, (2) Data reduction, (3) Data display, and (4) Conclusion. The result of the research showed that, (1) Jokowi used three types of speech act based on Austin theory as follows (a) locutionary act, (b) illocutionary act, and (c) perlocutionary act. (2) Factors that influence the use of Jokowi’s speech act on Twitter are political factors, economic factors, and social factors.